relational community, dialogic knowledge construction, collaborative narratives, cardography, doctoral thesis. - Celso Luiz Prudente; João Paulo Pinto Có; Paulo Morais-Alexandre (Universidade Federal do Norte do Tocantins, 2021)
The article demonstrates the centrality of the academic concern, in the discipline Ethnic-Racial Relations, which is given by an observation of the different Brazilian filmographies. A Chanchada was the paroxysm of the stereotype of racial inferiority of the image of the Iberian-Afro-American as a rural ethnic demand of Amerindian heritage in the progress-averse Jeca Tatu. To affirm the racial superiority of the imagetic hegemony of the Euro-hetero-macho-authoritarian as a sign of divine perfection expressed in the priest as God's representative. Racial domination determined by the power of euroheteronormativity. Cinema Novo was the trend that the black man became an aesthetic referent in the Marxist-influenced Glauberian realization. In the syntax of Cinema Novo in the semiotics of class struggles, the black man is a proletarian expression and the white man configures the bourgeoisie. The ontological struggle to affirm the positive image of minorities is a projection of class struggles. In Black Cinema, the Africanity that is a reference in Cinema Novismo conquers the position of subject in this cinema as the author of its own history. It concludes that it is in the Pedagogical Dimension of Black Cinema, as epistemic cinema that the minority builds the image of positive affirmation representing the visual of the decanted place of speech, as inclusive contemporaneity, overcoming the excluding anachronism.